The Moderating Role of Religiosity in the Relationship Between Social Media Use and Social Concern Among Indonesian Adolescents - Suprapto, Budi (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
Social concern represents the moral and behavioral manifestation of empathy, responsibility, and prosocial engagement in addressing societal problems. Religiosity, as a deeply internalized system of belief and moral commitment, has long been recognized as a potential source of prosocial motivation. Meanwhile, social media has emerged as both a powerful channel for mobilizing collective compassion and a potential driver of self-centered or performative behavior. This study examines how religiosity moderates the relationship between social media use and social concern among senior high school students in Malang City, Indonesia. Employing a quantitative explanatory design with a sample of 414 respondents selected through stratified sampling, data were collected using a structured questionnaire and analyzed through Moderated Regression Analysis (MRA). After reanalysis and correction, the regression model shows that religiosity significantly strengthens the positive effect of social media use on social concern. The adjusted coefficient of determination (R²) increased modestly from 0.04 to 0.07 after including the interaction term, indicating that religiosity serves as a meaningful moderator in this relationship. This finding suggests that adolescents with higher religiosity levels are more likely to transform social media exposure into altruistic and socially responsible behavior. The study contributes to the sociology of religion and communication studies by offering an empirical model linking digital engagement and faith-based values in promoting social solidarity.